Вплив “гомерівського питання” на своєрідність літературної трансформації “Одіссеї” (теоретичні аспекти) - Якубовська, Н. О. (К.: Видавничий Дім Дмитра Бураго, 2004)
У роботі розглядаються теоретичні аспекти дослідження «гомерівського питання» та його звʼязок з інтерпретаційними особливостями «Одіссеї» в літературі XX століття. The present work deals with the theoretical aspects of «Homeric question» studying and its connection with interpretation features of «Odysseus» in the XX century literature. The made research traces influence of the poem origin theories on forms and ways of reconsideration of the traditional plot. Key words: homeric question, interpretation, plot, image.
Keywords: гомерівське питання; інтерпретація; сюжет; образ